Pengaruh Kepuasan Dan Kepercayaan Konsumen Terhadap Loyalitas Merek Dengan Switching Cost Sebagai Variabel Mediasi (Studi Kasus Pada Konsumen Minyak Kayu Putih Cap Lang) Di Kota Madiun - Apriyanti Apriyanti; Heny Setyowati; Metik Asmike (UNIVERSITAS PGRI MADIUN, 2021)
This study is aimed to analyze the effect of consumer satisfaction, Consumer Trust, and Switching cost to Brand Loyality. The aim of this study are 1) To analyze the effect of consumer satisfaction to switching cost, 2) To analyze the effect of consumer trust to switching cost, 3) To analyze the effect of switching cost to brand loyality, 4) To analyze the effect of consumer satisfaction to brand loyality, 5) To analyze the effect of consumer trust to brand loyality. There were 154 respondents in this research. The sample deciding method is purposive sampling. To gain the result as the research goal, structural equation modelling SEM were analyzed by analysis moment of structure (AMOS) 21. The results shows that 1) consumer satisfaction positive and significantly effects the switching cost, 2) consumer trust positive and significantly effects the switching cost, 3) switching cost positive and significantly effects the brand loyality, 4) consumer satisfaction positive and significantly effect the brand loyality, 5) consumer trust positive and not significantly effect the brand loyality.